Production process of a building thermal insulation material
Patent Information
- Application Number
- CN202611049473.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
[0008]为此,本发明提供一种建筑用隔热保温材料的生产工艺,用以克服现有技术中聚苯乙烯保温材料的发泡过程无序不可控,并因局部破损导致隔热性能不可逆衰减,导致的隔热保温性能急剧下降的问题
[0019]与现有技术相比,本发明的有益效果在于,本发明通过油相材料与水相材料的共混形成水包油型乳液,以进行悬浮聚合反应得到尺寸均一的含气微囊,实现了隔热单元的结构可控,避免了传统工艺下泡孔结构波动大的缺陷,并通过对含气微囊进行改性处理,使在微囊表面原位引入能与聚合物基体形成强界面键合的活性官能团,解决了含气微囊在聚合物基体中因相容性差而导致的团聚的问题,并且改性微囊在模压成型的高温高压环境中,充当稳定的成核点和应力集中点,引导基体材料围绕其有序固化,塑造出预定形态、尺寸稳定的宏观封闭空腔,创造了受控的隔热单元,从而当宏观封闭空腔因冲击或应力而贯穿破损时,其内部的含气微囊作为微观隔热单元依然在发挥作用,使得材料在发生物理损伤时的隔热性能仅是部分降低,而非传统材料的功能完全失效。
Smart Images

Figure CN122896331A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal insulation material production technology, and in particular to a production process for thermal insulation materials for buildings. Background Technology
[0002] Building insulation materials primarily achieve their insulation function by constructing porous or honeycomb structures, utilizing the low thermal conductivity of still air. Existing technologies, such as polystyrene foam boards and rigid polyurethane foam, generally employ chemical or physical foaming processes to generate bubbles in situ within the polymer matrix. These foaming processes have the following inherent drawbacks: During the foaming process, the nucleation sites of bubbles are random and the nucleation density is uncontrollable, resulting in a wide distribution of cell size and unstable thermal insulation performance. The decomposition temperature of chemical foaming agents is difficult to precisely match with the polymer melting temperature. If decomposition occurs too early, gas escapes; if decomposition occurs too late, cells cannot grow sufficiently. Physical foaming, on the other hand, is strongly influenced by the coupling effect of gas solubility and melt temperature, resulting in an extremely narrow process window and large fluctuations in product quality.
[0003] The lack of effective constraints during the bubble growth stage leads to a significant "Ostwald ripening" effect, where large pores engulf small pores, resulting in polarization of pore sizes within the material and severely affecting the uniformity of thermal insulation. When the melt strength is insufficient after foaming, cell collapse and merging become severe, especially in large-sized products.
[0004] The thermal insulation performance of polystyrene foam insulation boards depends entirely on the integrity of their internal closed-cell structure. Once cracks or damage occur on the surface or inside the material, the closed-cell structure is destroyed, allowing outside air convection to enter, causing a sharp increase in thermal conductivity and a significant decrease in insulation performance. This decrease is irreversible; the damaged air bubbles cannot be resealed, and the insulation function is permanently lost.
[0005] Chinese Patent Application Publication No. CA118931060A discloses a high-temperature resistant insulation board and its preparation method. The high-temperature resistant insulation board comprises the following substances in parts by weight: 75-90 wt% polystyrene, 5-10 wt% reinforcing material, 0.5-3 wt% nucleating agent, 1-5 wt% flame retardant, and 5-10 wt% foaming agent. The reinforcing material includes any one or more of polyamide 6, ABS, and PC, and further includes magnetically expanded graphite. The preparation method is as follows: S1, raw material preparation; S2, insulation board preparation.
[0006] However, the aforementioned high-temperature resistant insulation board and its preparation method have the following problems: 1. The fundamental problems of bubbles still being generated in situ during the foaming process, random nucleation sites, and uncontrollable cell size have not been solved. Once the foaming process parameters fluctuate, defects will occur in the cell structure, resulting in unstable thermal insulation performance.
[0007] 2. When air bubbles in the insulation board burst, the bursting point will permanently lose its insulation function, causing an irreversible increase in thermal conductivity and a significant reduction in insulation performance. Summary of the Invention
[0008] Therefore, the present invention provides a production process for building thermal insulation materials to overcome the problems of disordered and uncontrollable foaming process of polystyrene insulation materials in the prior art, and irreversible attenuation of thermal insulation performance due to local damage, resulting in a sharp decline in thermal insulation performance.
[0009] To achieve the above objectives, the present invention provides a manufacturing process for thermal insulation materials for buildings, comprising: A mixture of aqueous and oil phase materials is placed in a high-speed shear emulsifier for emulsification to obtain an oil-in-water emulsion. The oil-in-water emulsion was transferred to a high-pressure reactor, and an inert gas was introduced into the reactor to replace the air inside, so as to carry out a suspension polymerization reaction and obtain gas-containing microcapsules. The gas-containing microcapsules were dispersed in anhydrous ethanol to obtain a suspension, and the suspension was modified by adding a silane coupling agent to introduce active functional groups on the surface of the gas-containing microcapsules to obtain modified gas-containing microcapsules. The modified gas-containing microcapsules are blended with a matrix material to obtain a blended material. The blended material is then heated and melted and molded to form a blank structure with a closed cavity inside during the molding process. After demolding, a heat-insulating board blank with a closed cavity inside is obtained. The closed cavity of the insulation board blank is vacuumed and filled with heat-insulating gas, so that the heat-insulating gas is sealed inside the closed cavity to obtain a heat-insulating material for building. The aqueous phase material comprises the following components in parts by mass: 100 parts deionized water, 1.0 to 5.0 parts dispersant, and 0.1 to 1.0 parts co-dispersant; The oil phase material comprises the following components in parts by weight: 100 parts of olefin monomers, 0.5 to 3.0 parts of crosslinking agent, 0.5 to 2.0 parts of initiator, and 10 to 30 parts of liquid hydrocarbon foaming agent.
[0010] Furthermore, the process of obtaining gas-containing microcapsules includes, The mixture of oil phase material and water phase material is placed in a high-speed shear emulsifier and sheared at a speed of 15000 rpm for 10 to 15 minutes to form an oil-in-water emulsion. The oil-in-water emulsion was transferred to a high-pressure reactor, and after the air inside the reactor was replaced by inert gas, the reactor was sealed. The suspension polymerization reaction was carried out at a polymerization temperature of 60℃~80℃ and a stirring speed of 100rpm~300rpm for 24 hours to obtain an air-containing microcapsule slurry. The gas-containing microcapsule slurry was placed in a centrifuge for solid-liquid separation, and the solids were collected. The solids were washed with deionized water 3 to 5 times and then placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain gas-containing microcapsules.
[0011] Furthermore, the process of obtaining modified gas-containing microcapsules includes, The gas-containing microcapsules were dispersed in anhydrous ethanol to prepare a suspension with a gas-containing microcapsule mass fraction of 5% to 20%. A silane coupling agent was added to the suspension, and the mixture was reacted for 2 to 6 hours at a stirring speed of 200 rpm to 400 rpm under a temperature of 40°C to 60°C. After the reaction was completed, the reaction solution was placed in a centrifuge for solid-liquid separation, and the modified solid was collected. The modified solid was washed 2-3 times with anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 60°C for 6 hours to obtain modified gas-containing microcapsules with active functional groups on the surface.
[0012] Furthermore, the molding process includes, Modified gas-containing microcapsules and polystyrene resin were fed into an internal mixer at a mass ratio of 20:100 to 35:100 and heated to 180℃ to 220℃, and melted and plasticized at a rotor speed of 50rpm to 100rpm. After melting and plasticizing, the mixture is stirred at a speed of 150 rpm to 500 rpm for 10 to 30 minutes to uniformly disperse the modified gas-containing microcapsules in the polystyrene melt, thus obtaining a composite melt. The composite melt is transferred to a molding machine and molded at a molding temperature of 175℃~200℃ and a molding pressure of 10MPa~15MPa. The pressure holding time is 20~40 minutes. After cooling to 60℃~80℃, the mold is opened and the melt is removed to obtain a thermal insulation board blank with a closed cavity inside.
[0013] Furthermore, the process of obtaining building insulation materials includes, An air inlet is opened on the surface of the insulation board blank, which is connected to the closed cavity; The sealed cavity is evacuated through the air inlet to remove the original air and put it under negative pressure. The vacuum is evacuated to a vacuum level of -0.08MPa to -0.095MPa for 5 to 15 minutes. After the vacuum is completed, heat-insulating gas is injected into the sealed cavity through the gas inlet until the gauge pressure is 0.05MPa to 0.5MPa; After inflation, the inflation port is sealed to enclose the insulating gas inside the closed cavity, thus obtaining a building insulation material.
[0014] Furthermore, the liquid hydrocarbon foaming agent is one of n-pentane, isopentane, n-hexane, or isohexane, with a boiling point of 30°C to 85°C.
[0015] Furthermore, the olefin monomer is selected from one of acrylonitrile, methacrylonitrile, methyl methacrylate, methyl acrylate, and styrene.
[0016] Furthermore, the gas-containing microcapsules have a particle size of 5μm to 80μm, a shell thickness of 0.5μm to 5μm, and the shell material is a cross-linked copolymer of olefin monomers. The interior is filled with gas formed after the liquid hydrocarbon foaming agent is heated and vaporized.
[0017] Furthermore, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane, and the amount used is 1.0% to 5.0% of the mass of the gas-containing microcapsules.
[0018] Furthermore, the insulating gas is one of nitrogen, argon, or carbon dioxide.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention forms an oil-in-water emulsion by blending oil-phase materials and water-phase materials, and then performs a suspension polymerization reaction to obtain gas-containing microcapsules with uniform size. This achieves controllable structure of the thermal insulation unit, avoiding the defect of large fluctuations in the pore structure under traditional processes. Furthermore, by modifying the gas-containing microcapsules, active functional groups that can form strong interfacial bonds with the polymer matrix are introduced in situ on the surface of the microcapsules, solving the problem of agglomeration of gas-containing microcapsules in the polymer matrix due to poor compatibility. In addition, the modified microcapsules act as stable nucleation points and stress concentration points in the high temperature and high pressure environment of compression molding, guiding the matrix material to solidify around them in an orderly manner, shaping a macroscopic closed cavity with a predetermined shape and stable size, and creating a controlled thermal insulation unit. Thus, when the macroscopic closed cavity is damaged by impact or stress, the gas-containing microcapsules inside still function as microscopic thermal insulation units, so that the thermal insulation performance of the material is only partially reduced when physical damage occurs, rather than the complete failure of the function of traditional materials.
[0020] Furthermore, this invention transforms the oil-water phase mixture into a water-in-oil emulsion with uniform particle size through high-speed shear emulsification, ensuring the size consistency of the microcapsule structure. This solves the problem of uncontrollable insulation units caused by random bubble nucleation and discrete distribution in traditional foaming processes. Suspension polymerization is carried out under inert gas protection, allowing olefin monomers to crosslink and polymerize in an oxygen-free environment. This forms a dense and controllable three-dimensional network shell at the oil droplet interface, effectively encapsulating the liquid foaming agent and preventing its escape. This completely avoids the interference of moisture and oxygen in the air on the polymerization reaction, ensuring the integrity and airtightness of the microcapsule shell.
[0021] Furthermore, this invention modifies the gas-containing microcapsules to form strong siloxane bonds between the siloxane groups in the silane molecules and the hydroxyl groups on the surface of the microcapsule shell. At the same time, the methacryloyloxy or amino groups at the organic end interact strongly with the polystyrene matrix, achieving a chemical bonding transition from the microcapsule surface to the polymer matrix. This allows the originally hydrophobic microcapsules and oleophilic resin to be uniformly dispersed during the melt blending stage, avoiding agglomeration and interfacial debonding. This ensures that the microcapsules can stably act as nucleation sites during compression molding, guiding the formation of regular and orderly macroscopic closed cavities. This solves the problem of decreased mechanical properties and thermal bridging effects caused by interfacial weakening in traditional composite materials.
[0022] Furthermore, this invention utilizes the active functional groups introduced on the surface of the gas-containing microcapsules to melt-blend with a polystyrene matrix material, thereby improving the interfacial bonding between the microcapsules and the matrix and ensuring uniform dispersion of the microcapsules in the melt. This allows the composite melt to form a preform structure with a closed cavity during molding, achieving controllable construction and uniform distribution of the closed cavity within the preform. This overcomes the problem of accurately controlling the pore size and distribution in traditional foaming methods. By vacuuming the closed cavity of the insulation board preform, residual air is removed, and a low thermal conductivity insulating gas is filled in and sealed. This encloses the insulating gas within the cavity, forming a dual thermal insulation barrier of microcapsule encapsulation and cavity encapsulation. This suppresses gas convection and heat radiation transfer, thus ensuring the thermal insulation stability of the building insulation material during long-term service. Attached Figure Description
[0023] Figure 1 This is a flowchart illustrating the production process of thermal insulation materials for buildings according to an embodiment of the present invention. Figure 2 This is a flowchart illustrating the steps involved in obtaining gas-containing microcapsules according to an embodiment of the present invention. Figure 3 This is a flowchart illustrating the steps involved in obtaining modified gas-containing microcapsules according to an embodiment of the present invention. Figure 4 This is a flowchart of the molding process steps in an embodiment of the present invention. Detailed Implementation
[0024] To make the objectives and advantages of the present invention clearer, the present invention will be further described below with reference to embodiments; it should be understood that the specific embodiments described herein are merely for explaining the present invention and are not intended to limit the present invention.
[0025] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.
[0026] Please see Figure 1 The diagram shown is a flowchart illustrating the production process of the building insulation material according to an embodiment of the present invention. The production process of the building insulation material in this embodiment includes: Step S1: The mixture of aqueous and oil phase materials is placed in a high-speed shear emulsifier for emulsification to obtain an oil-in-water emulsion. Step S2: The oil-in-water emulsion is transferred to a high-pressure reactor, and an inert gas is introduced into the high-pressure reactor to replace the air inside the reactor in order to carry out a suspension polymerization reaction and obtain gas-containing microcapsules. Step S3: Disperse the gas-containing microcapsules in anhydrous ethanol to obtain a suspension, and add a silane coupling agent to the suspension for modification treatment, so as to introduce active functional groups on the surface of the gas-containing microcapsules to obtain modified gas-containing microcapsules. Step S4: The modified gas-containing microcapsules are blended with the matrix material to obtain a blended material. The blended material is heated and melted and then molded to form a blank structure with a closed cavity inside during the molding process. After demolding, a heat-insulating board blank with a closed cavity inside is obtained. Step S5: Vacuum the closed cavity of the insulation board blank and fill it with heat insulation gas to seal the heat insulation gas inside the closed cavity, thereby obtaining the building heat insulation material.
[0027] In this embodiment, the oil phase material comprises the following components in parts by mass: 100 parts of olefin monomers, 0.5 to 3.0 parts of crosslinking agent, 0.5 to 2.0 parts of initiator, and 10 to 30 parts of liquid hydrocarbon foaming agent.
[0028] The olefin monomer is selected from one of acrylonitrile, methacrylonitrile, methyl methacrylate, methyl acrylate, and styrene.
[0029] The crosslinking agent is divinylbenzene or trimethylolpropane trimethacrylate.
[0030] The initiator is azobisisobutyronitrile or benzoyl peroxide.
[0031] The liquid hydrocarbon foaming agent is one of n-pentane, isopentane, n-hexane, or isohexane, with a boiling point of 30℃ to 85℃.
[0032] In this embodiment, the aqueous phase material comprises the following components in parts by mass: 100 parts deionized water, 1.0 to 5.0 parts dispersant, and 0.1 to 1.0 parts co-dispersant.
[0033] The dispersant is polyvinyl alcohol or polyethylene glycol.
[0034] The dispersant is sodium dodecyl sulfate or sodium dodecylbenzenesulfonate.
[0035] Specifically, in this embodiment of the invention, an oil-in-water emulsion is formed by blending oil-phase materials and aqueous-phase materials to conduct a suspension polymerization reaction, resulting in uniformly sized gas-containing microcapsules. This achieves controllable structure of the thermal insulation unit, avoiding the defects of large fluctuations in the pore structure under traditional processes. Furthermore, by modifying the gas-containing microcapsules, active functional groups that can form strong interfacial bonds with the polymer matrix are introduced in situ on the surface of the microcapsules, solving the problem of agglomeration of gas-containing microcapsules in the polymer matrix due to poor compatibility. In the high-temperature and high-pressure environment of compression molding, the modified microcapsules act as stable nucleation points and stress concentration points, guiding the matrix material to solidify around them in an orderly manner, shaping a macroscopically closed cavity with a predetermined shape and stable size, creating a controlled thermal insulation unit. Thus, when the macroscopically closed cavity is damaged by impact or stress, the gas-containing microcapsules inside still function as microscopic thermal insulation units, ensuring that the thermal insulation performance of the material is only partially reduced when physical damage occurs, rather than the complete failure of the function of traditional materials.
[0036] Please see Figure 2 The diagram shown is a flowchart illustrating the steps involved in obtaining gas-containing microcapsules according to an embodiment of the present invention. In this embodiment, the process of obtaining gas-containing microcapsules includes: Step S21: Place the mixture of oil phase material and water phase material in a high-speed shear emulsifier and shear it at a speed of 15000 rpm for 10 to 15 minutes to form an oil-in-water emulsion. Step S22: The oil-in-water emulsion is transferred to a high-pressure reactor, and an inert gas is introduced to replace the air in the reactor. The reactor is then sealed, and a suspension polymerization reaction is carried out at a polymerization temperature of 60℃~80℃ and a stirring speed of 100rpm~300rpm for 24 hours to obtain an air-containing microcapsule slurry. Step S23: The gas-containing microcapsule slurry is placed in a centrifuge for solid-liquid separation, the solids are collected, the solids are washed with deionized water 3 to 5 times and then placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain gas-containing microcapsules.
[0037] In this embodiment, during the suspension polymerization reaction, olefin monomers undergo free radical polymerization under the action of an initiator, and the crosslinking agent causes the polymer molecular chains to form a three-dimensional network structure. The crosslinked polymer shell is gradually precipitated and deposited at the interface of the oil phase droplets, while the liquid hydrocarbon foaming agent is coated inside the shell.
[0038] In this embodiment, the particle size of the gas-containing microcapsules is 5μm to 80μm, the shell thickness is 0.5μm to 5μm, the shell material is a cross-linked copolymer of olefin monomers, and the interior is filled with gas formed by the vaporization of the liquid hydrocarbon foaming agent after heating.
[0039] Specifically, this invention transforms a mixture of oil and water phases into a water-in-oil emulsion with uniform particle size through high-speed shear emulsification, ensuring the size consistency of the microcapsule structure. This solves the problem of uncontrollable insulation units caused by random bubble nucleation and discrete distribution in traditional foaming processes. Furthermore, suspension polymerization is carried out under inert gas protection, allowing olefin monomers to crosslink and polymerize in an oxygen-free environment. This forms a dense and controllable three-dimensional network shell at the oil droplet interface, effectively encapsulating the liquid foaming agent and preventing its escape. This completely avoids interference from moisture and oxygen in the air on the polymerization reaction, ensuring the integrity and airtightness of the microcapsule shell.
[0040] Please see Figure 3 The diagram shown is a flowchart illustrating the steps involved in obtaining modified gas-containing microcapsules according to an embodiment of the present invention. In this embodiment, the process of obtaining modified gas-containing microcapsules includes: Step S31: Disperse the gas-containing microcapsules in anhydrous ethanol to prepare a suspension with a gas-containing microcapsule mass fraction of 5% to 20%. Step S32: Add silane coupling agent to the suspension and react for 2 to 6 hours at a stirring speed of 200 rpm to 400 rpm under a temperature of 40°C to 60°C. Step S33: After the reaction is completed, the reaction solution is placed in a centrifuge for solid-liquid separation, and the modified solid is collected. The modified solid is washed 2-3 times with anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 60°C for 6 hours to obtain modified gas-containing microcapsules with active functional groups on the surface.
[0041] In this embodiment, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane, and the amount used is 1.0% to 5.0% of the mass of the gas-containing microcapsules.
[0042] Specifically, the embodiments of the present invention modify the gas-containing microcapsules to form strong siloxane bonds between the siloxane groups in the silane molecules and the hydroxyl groups on the surface of the microcapsule shell. At the same time, the methacryloyloxy or amino groups at the organic end interact strongly with the polystyrene matrix, achieving a chemical bonding transition from the microcapsule surface to the polymer matrix. This allows the originally hydrophobic microcapsules and oleophilic resin to be uniformly dispersed during the melt blending stage, avoiding agglomeration and interfacial debonding. This ensures that the microcapsules can stably act as nucleation sites during compression molding, guiding the formation of regular and orderly macroscopic closed cavities. This solves the problem of decreased mechanical properties and thermal bridging effects caused by interfacial weakening in traditional composite materials.
[0043] Please see Figure 4 The diagram shown is a flowchart of the molding process according to an embodiment of the present invention. In this embodiment, the molding process includes... Step S41: The modified gas-containing microcapsules and polystyrene resin are fed into an internal mixer at a mass ratio of 20:100 to 35:100, heated to 180°C to 220°C, and melted and plasticized at a rotor speed of 50 rpm to 100 rpm. Step S42: After melting and plasticizing, mix at a stirring speed of 150 rpm to 500 rpm for 10 to 30 minutes to uniformly disperse the modified gas-containing microcapsules in the polystyrene melt and obtain a composite melt. Step S43: The composite melt is transferred to a molding machine and molded at a molding temperature of 175℃~200℃ and a molding pressure of 10MPa~15MPa for 20~40 minutes. After cooling to 60℃~80℃, the mold is opened and the melt is removed to obtain a heat-insulating board blank with a closed cavity inside.
[0044] In this embodiment, the cavity surface of the mold used for compression molding is provided with a number of raised structures arranged in an array. The height of the raised structures is consistent with the depth of the closed cavity. The shape of the raised structures is spherical or ellipsoidal. During compression molding, the composite melt fills the mold cavity under pressure. The raised structures occupy the corresponding space inside the melt, causing the melt to be squeezed and flow around the raised structures. After cooling and solidification, the mold is demolded. The location of the raised structures forms a heat-insulating board blank with a closed cavity inside. The arrangement spacing of the raised structures is determined according to the required cavity wall thickness between adjacent closed cavities.
[0045] In this embodiment, the process of obtaining building thermal insulation material includes, An air inlet is opened on the surface of the insulation board blank, which is connected to the closed cavity; The sealed cavity is evacuated through the air inlet to remove the original air and put it under negative pressure. The vacuum is evacuated to a vacuum level of -0.08MPa to -0.095MPa for 5 to 15 minutes. After the vacuum is completed, heat-insulating gas is injected into the sealed cavity through the gas inlet until the gauge pressure is 0.05MPa to 0.5MPa; After inflation, the inflation port is sealed to seal the insulating gas inside the closed cavity, thus obtaining a building insulation material. In this embodiment, the sealing method is heat sealing, the heat sealing temperature is 150℃~200℃, and the heat sealing pressure is 0.2MPa~0.5MPa.
[0046] In this embodiment, the air inlet is opened by mechanical drilling at a position corresponding to the center of each closed cavity on the surface of the insulation board blank. The drilling depth is to penetrate the surface of the board to the inside of the closed cavity. The diameter of the air inlet is 1mm to 3mm. The air inlet forms a microporous channel connecting the closed cavity with the external environment, which is used for vacuuming and inflation operations.
[0047] In this embodiment, the insulating gas is one of nitrogen, argon, or carbon dioxide.
[0048] Specifically, this invention involves melt-blending modified gas-containing microcapsules with a polystyrene matrix material. The active functional groups introduced onto the surface of the gas-containing microcapsules improve the interfacial bonding with the matrix, ensuring uniform dispersion of the microcapsules in the melt. Through compression molding, the composite melt forms a blank structure with a closed cavity inside, achieving controllable construction and uniform distribution of the closed cavity within the blank. This overcomes the problem of precisely controlling pore size and distribution in traditional foaming methods. Furthermore, by vacuuming the closed cavity of the insulation board blank, residual air is removed, and a low thermal conductivity insulating gas is filled in and sealed. This encloses the insulating gas within the cavity, forming a dual thermal insulation barrier of microcapsule encapsulation and cavity encapsulation. This suppresses gas convection and heat radiation transfer, thereby ensuring the thermal insulation stability of the building insulation material during long-term service. Example
[0049] The oil phase material and the water phase material are mixed at a mass ratio of 1:5, and the mixture of oil phase material and water phase material is placed in a high-speed shear emulsifier and sheared at a speed of 15000 rpm for 10 minutes to form an oil-in-water emulsion. The oil-in-water emulsion was transferred to a high-pressure reactor, nitrogen was introduced to replace the air in the reactor, and the reactor was sealed. The suspension polymerization reaction was carried out at a polymerization temperature of 65°C and a stirring speed of 200 rpm for 24 hours to obtain an air-containing microcapsule slurry. The gas-containing microcapsule slurry was placed in a centrifuge for solid-liquid separation, and the solids were collected. The solids were washed four times with deionized water and then placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain gas-containing microcapsules. 10g of the gas-containing microcapsules were dispersed in 100g of anhydrous ethanol and stirred at 300rpm for 15 minutes at room temperature to obtain a suspension with a gas-containing microcapsule mass fraction of 9.1%. 0.3 g of γ-methacryloxypropyltrimethoxysilane was added to the suspension, and the mixture was reacted at 50 °C and a stirring speed of 300 rpm for 4 hours. After the reaction was completed, the reaction solution was placed in a centrifuge for solid-liquid separation, and the modified solid was collected. The modified solid was washed three times with anhydrous ethanol and then placed in a vacuum drying oven. It was vacuum dried at 50°C for 8 hours to obtain modified gas-containing microcapsules with carbon-carbon double bond active functional groups grafted on the surface. 100g of polystyrene resin was put into a mixer and heated to 200°C. The mixture was melted and plasticized at a rotor speed of 80 rpm. 15g of the modified gas-containing microcapsules were added to the molten polystyrene and mixed at a stirring speed of 300 rpm for 20 minutes to uniformly disperse the modified gas-containing microcapsules in the polystyrene melt, thus obtaining a composite melt.
[0050] The composite melt is transferred to a molding machine and molded at a molding temperature of 185°C and a molding pressure of 12MPa. The pressure is held for 30 minutes, and after cooling to 70°C, the mold is opened and the melt is removed to obtain a thermal insulation board blank with a closed cavity inside. An air inlet is opened on the surface of the insulation board blank and connected to the closed cavity, so as to perform vacuum treatment on the closed cavity through the air inlet, and the vacuum is evacuated to a vacuum degree of -0.09MPa for 10 minutes. After the vacuum is completed, nitrogen gas is introduced into the sealed cavity through the gas inlet until the gauge pressure is 0.2 MPa; After inflation, the inflation port is heat-sealed at a temperature of 180°C and a pressure of 0.3 MPa to seal the nitrogen gas inside the closed cavity, thus obtaining a thermal insulation material for buildings.
[0051] In this embodiment, the oil phase material comprises the following components: 30 parts acrylonitrile, 20 parts methyl methacrylate, 1.5 parts divinylbenzene, 1.0 part azobisisobutyronitrile, and 15 parts n-pentane; the aqueous phase material comprises the following components: 100 parts deionized water, 3 parts polyvinyl alcohol, and 0.5 parts sodium dodecyl sulfate.
[0052] In this embodiment, the particle size of the gas-containing microcapsules is 20μm to 50μm, and the shell thickness is 1μm to 3μm.
[0053] In this embodiment, the equivalent diameter of the enclosed cavity is 20mm, the wall thickness between adjacent enclosed cavities is 3mm, and the volume of the enclosed cavity accounts for 40% of the total volume of the plate.
[0054] In this embodiment, the insulation board blank is a rectangular flat plate structure with several closed cavities evenly distributed in an array inside. The closed cavities are spherical or ellipsoidal, and each closed cavity is separated by a cavity wall formed of polystyrene matrix material with a cavity wall thickness of 3mm. The surface of the closed cavities is smooth and free of air bubbles. An air inlet is provided on the upper surface of the board at a position corresponding to the center of each closed cavity. The air inlet is a microporous channel that penetrates the surface of the board to the inside of the closed cavity. The diameter of the air inlet is smaller than the equivalent diameter of the closed cavity. After heat sealing, the air inlet is completely sealed, and the surface of the board is flat and free of protrusions. The overall thickness of the insulation board blank is 50mm, the length is 600mm, and the width is 600mm. Example
[0055] The difference from Example 1 is that the crosslinking agent is trimethylolpropane trimethacrylate, and the amount used is 2.0 parts. The remaining steps are the same as in Example 1. Example
[0056] The difference from Example 1 is that the liquid hydrocarbon foaming agent is isopentane, and the amount used is 20 parts. The remaining steps are the same as in Example 1. Example
[0057] The difference from Example 1 is that the olefin monomers are 25 parts of methacrylonitrile and 25 parts of styrene, totaling 50 parts, replacing 30 parts of acrylonitrile and 20 parts of methyl methacrylate in Example 1. The remaining steps are the same as in Example 1. Example
[0058] The difference from Example 1 is that the silane coupling agent is γ-aminopropyltriethoxysilane, and the amount used is 3.0% of the mass of the gas-containing microcapsules, that is, 0.3g. The remaining steps are the same as in Example 1. Example
[0059] The difference from Example 1 is that the amount of modified gas-containing microcapsules added is 10% of the mass of polystyrene resin, that is, 10g. The remaining steps are the same as in Example 1. Example
[0060] The difference from Example 1 is that the equivalent diameter of the closed cavity is 10mm, the wall thickness between adjacent closed cavities is 2mm, and the volume of the closed cavity accounts for 50% of the total volume of the board. The remaining steps are the same as in Example 1. Example
[0061] The difference from Example 1 is that the insulating gas is argon, and it is filled to a gauge pressure of 0.2 MPa. The remaining steps are the same as in Example 1.
[0062] Comparative Example 1 The difference from Example 1 is that no gas-containing microcapsules are prepared or added. 100g of polystyrene resin is put into a mixer for melting and plasticizing without adding gas-containing microcapsules to obtain pure polystyrene melt. It is then molded at a molding temperature of 185°C and a molding pressure of 12MPa, held under pressure for 30 minutes, cooled to 70°C, and then demolded to obtain a heat-insulating board blank with a closed cavity inside. Nitrogen gas is then introduced into the cavity to a gauge pressure of 0.2MPa and then heat-sealed. The remaining steps are the same as in Example 1.
[0063] In this comparative example, the equivalent diameter of the enclosed cavity is 20 mm, the wall thickness between adjacent enclosed cavities is 3 mm, and the volume of the enclosed cavity accounts for 40% of the total volume of the plate.
[0064] Comparative Example 2 The difference from Example 1 is that a regular flat mold is used in the compression molding process, without setting up a protruding structure to form a closed cavity, and directly compression molding into a solid flat blank without constructing a closed cavity. The remaining steps are the same as in Example 1.
[0065] Comparative Example 3 The difference from Example 1 is that unmodified gas-containing microcapsules are blended with polystyrene resin, while the rest of the steps are the same as in Example 1.
[0066] Comparative Example 4 Polystyrene insulation boards are prepared using the existing EPS foaming process. Expandable polystyrene beads containing the foaming agent pentane are pre-foamed and cured, then placed in a mold and heated to 110°C with steam to foam and form the boards. This causes the beads to expand a second time and fuse together. After cooling and demolding, EPS insulation boards are obtained.
[0067] In this comparative example, the density of the board is 30 kg / m³.
[0068] Comparative Example 5 The difference from Example 1 is that no vacuuming is performed. Nitrogen gas is filled into the sealed cavity through the gas filling port until the gauge pressure is 0.2 MPa, and then the cavity is heat-sealed. The remaining steps are the same as in Example 1.
[0069] The thermal insulation materials for building use prepared in Examples 1-8 and Comparative Examples 1-5 were subjected to performance tests.
[0070] Table 1 Performance Testing Methods
[0071] Table 2 Performance test results of the embodiments
[0072] Table 3 Comparative Performance Test Results
[0073] As shown in Table 2, the initial thermal conductivity of Examples 1-8 ranges from 0.023 W / (m·K) to 0.028 W / (m·K), which is significantly lower than that of existing EPS boards (0.033-0.036 W / (m·K)). Among them, Example 7 has the lowest initial thermal conductivity at 0.023 W / (m·K), indicating that the higher the volume ratio of the closed cavity and the smaller the equivalent diameter, the better the thermal insulation performance. No air bubbles escaped from the cavity airtightness test of all examples, proving that the heat-sealed seal has good sealing reliability.
[0074] Furthermore, the thermal conductivity increase rate after damage in Examples 1-8 was between 37.0% and 41.7%. Taking Example 1 as an example, the thermal conductivity before damage was 0.025 W / (m·K), and after damage it was 0.035 W / (m·K), with an increase rate of 40.0%. This indicates that even if the board has a through crack, its thermal conductivity remains at a low level, and the heat insulation function is not lost due to local damage.
[0075] After 10 thermal cycles, the thermal conductivity of Examples 1-8 increased by only 0.002 to 0.003 W / (m·K), which is less than 10%, indicating that the material has good resistance to temperature changes and long-term thermal insulation stability. Furthermore, the water absorption rate of Examples 1-8 is only 1.0% to 1.4%, which is much lower than that of EPS foam board, proving that the dense surface layer formed by molding has excellent waterproof performance.
[0076] As shown in Table 3, in Comparative Example 1, there were no gas-containing microcapsules and no backup insulation unit after the cavity was damaged, resulting in a thermal conductivity increase rate of 103.1%. In Example 1, there were gas-containing microcapsules, and the microcapsules continued to function after the cavity was damaged, with an increase rate of only 40.0%. This demonstrates that gas-containing microcapsules are the structural basis for the fault tolerance function of thermal insulation materials used in buildings.
[0077] Comparative Example 3, with its unmodified gas-containing microcapsules, agglomerated in the matrix, forming defects. Its compressive strength was only 0.20 MPa, and the rate of increase after breakage was 67.7%. In contrast, Example 1, modified with a silane coupling agent, showed uniform microcapsules dispersion, increasing the compressive strength to 0.32 MPa and reducing the rate of increase to 40.0%. The difference in compressive strength between the two examples was 0.12 MPa, and the difference in the rate of increase was 27.7%. This demonstrates that surface modification is a technical guarantee for achieving uniform microcapsule dispersion and simultaneously improving mechanical and thermal insulation properties.
[0078] Comparative Example 2 had no enclosed cavity, with an initial thermal conductivity of 0.028 W / (m·K) and a subsequent thermal conductivity of 0.031 W / (m·K). Example 1 had a cavity, with the initial thermal conductivity decreasing to 0.025 W / (m·K) and then to 0.028 W / (m·K) after thermal cycling. The difference in initial thermal conductivity between the two examples was 0.003 W / (m·K), and the difference after thermal cycling was also 0.003 W / (m·K), demonstrating that the enclosed cavity contributes to improving initial thermal insulation performance and long-term durability.
[0079] Comparative Example 4 is an existing EPS foam board with an initial thermal conductivity of 0.034 W / (m·K). After damage, the thermal conductivity increases to 0.078 W / (m·K), an increase of 129.4%. After thermal cycling, the thermal conductivity is 0.052 W / (m·K), and the water absorption rate is 4.2%. All performance characteristics are significantly worse than those of Example 1. The EPS foam board uses a single-stage bubble system as the insulation structure. Once the bubble breaks, it becomes permanently ineffective. After damage, the thermal conductivity increases sharply, and the insulation performance is almost completely lost.
[0080] Comparative Example 5 was not evacuated, and residual air and water vapor remained in the cavity. The initial thermal conductivity was 0.028 W / (m·K). After the damage, the thermal conductivity increased by 46.4%, and after thermal cycling, the thermal conductivity was 0.033 W / (m·K), both of which were worse than Example 1. This proves that evacuation is a key step to ensure the purity of the gas in the cavity and guarantee long-term thermal stability.
[0081] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will all fall within the scope of protection of the present invention.
Claims
1. A production process for a building thermal insulation material, characterized in that, include: A mixture of aqueous and oil phase materials is placed in a high-speed shear emulsifier for emulsification to obtain an oil-in-water emulsion. The oil-in-water emulsion was transferred to a high-pressure reactor, and an inert gas was introduced into the reactor to replace the air inside, so as to carry out a suspension polymerization reaction and obtain gas-containing microcapsules. The gas-containing microcapsules were dispersed in anhydrous ethanol to obtain a suspension, and the suspension was modified by adding a silane coupling agent to introduce active functional groups on the surface of the gas-containing microcapsules to obtain modified gas-containing microcapsules. The modified gas-containing microcapsules are blended with a matrix material to obtain a blended material. The blended material is then heated and melted and molded to form a blank structure with a closed cavity inside during the molding process. After demolding, a heat-insulating board blank with a closed cavity inside is obtained. The closed cavity of the insulation board blank is vacuumed and filled with heat-insulating gas, so that the heat-insulating gas is sealed inside the closed cavity to obtain a heat-insulating material for building. The aqueous phase material comprises the following components in parts by mass: 100 parts deionized water, 1.0 to 5.0 parts dispersant, and 0.1 to 1.0 parts co-dispersant; The oil phase material comprises the following components in parts by weight: 100 parts of olefin monomers, 0.5 to 3.0 parts of crosslinking agent, 0.5 to 2.0 parts of initiator, and 10 to 30 parts of liquid hydrocarbon foaming agent.
2. The production process of the building thermal insulation material according to claim 1, characterized in that, The process of obtaining gas-containing microcapsules includes, The mixture of oil phase material and water phase material is placed in a high-speed shear emulsifier and sheared at a speed of 15000 rpm for 10 to 15 minutes to form an oil-in-water emulsion. The oil-in-water emulsion was transferred to a high-pressure reactor, and after the air inside the reactor was replaced by inert gas, the reactor was sealed. The suspension polymerization reaction was carried out at a polymerization temperature of 60℃~80℃ and a stirring speed of 100rpm~300rpm for 24 hours to obtain an air-containing microcapsule slurry. The gas-containing microcapsule slurry was placed in a centrifuge for solid-liquid separation, and the solids were collected. The solids were washed with deionized water 3 to 5 times and then placed in a vacuum drying oven and vacuum dried at 60°C for 12 hours to obtain gas-containing microcapsules.
3. The production process of the building thermal insulation material according to claim 1, characterized in that, The process of obtaining modified gas-containing microcapsules includes, The gas-containing microcapsules were dispersed in anhydrous ethanol to prepare a suspension with a gas-containing microcapsule mass fraction of 5% to 20%. A silane coupling agent was added to the suspension, and the mixture was reacted for 2 to 6 hours at a stirring speed of 200 rpm to 400 rpm under a temperature of 40°C to 60°C. After the reaction was completed, the reaction solution was placed in a centrifuge for solid-liquid separation, and the modified solid was collected. The modified solid was washed 2-3 times with anhydrous ethanol and then placed in a vacuum drying oven and vacuum dried at 60°C for 6 hours to obtain modified gas-containing microcapsules with active functional groups on the surface.
4. The production process of the building thermal insulation material according to claim 1, characterized in that, The molding process includes, Modified gas-containing microcapsules and polystyrene resin were fed into an internal mixer at a mass ratio of 20:100 to 35:100 and heated to 180℃ to 220℃, and melted and plasticized at a rotor speed of 50rpm to 100rpm. After melting and plasticizing, the mixture is stirred at a speed of 150 rpm to 500 rpm for 10 to 30 minutes to uniformly disperse the modified gas-containing microcapsules in the polystyrene melt, thus obtaining a composite melt. The composite melt is transferred to a molding machine and molded at a molding temperature of 175℃~200℃ and a molding pressure of 10MPa~15MPa. The pressure holding time is 20~40 minutes. After cooling to 60℃~80℃, the mold is opened and the melt is removed to obtain a thermal insulation board blank with a closed cavity inside.
5. The production process of the building thermal insulation material according to claim 1, characterized in that, The process of obtaining building insulation materials includes, An air inlet is opened on the surface of the insulation board blank, which is connected to the closed cavity; The sealed cavity is evacuated through the air inlet to remove the original air and put it under negative pressure. The vacuum is evacuated to a vacuum level of -0.08MPa to -0.095MPa for 5 to 15 minutes. After the vacuum is completed, heat-insulating gas is injected into the sealed cavity through the gas inlet until the gauge pressure is 0.05MPa to 0.5MPa; After inflation, the inflation port is sealed to enclose the insulating gas inside the closed cavity, thus obtaining a building insulation material.
6. The production process of the building thermal insulation material according to claim 1, characterized in that, The liquid hydrocarbon foaming agent is one of n-pentane, isopentane, n-hexane, or isohexane, with a boiling point of 30℃ to 85℃.
7. The production process of the building thermal insulation material according to claim 1, characterized in that, The olefin monomer is selected from one of acrylonitrile, methacrylonitrile, methyl methacrylate, methyl acrylate, and styrene.
8. The production process of the building thermal insulation material according to claim 2, characterized in that, The gas-containing microcapsules have a particle size of 5μm to 80μm and a shell thickness of 0.5μm to 5μm. The shell material is a cross-linked copolymer of olefin monomers, and the interior is filled with gas formed by the vaporization of the liquid hydrocarbon foaming agent upon heating.
9. The production process of the building thermal insulation material according to claim 3, characterized in that, The silane coupling agent is γ-methacryloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane, and the amount used is 1.0% to 5.0% of the mass of the gas-containing microcapsules.
10. The production process of the building thermal insulation material according to claim 5, characterized in that, The insulating gas is one of nitrogen, argon, or carbon dioxide.